El Sindicalismo y el Acceso al Decisor en Argentina. La Reforma Previsional Durante la Década de 1990. - Araya Moreno, Eduardo; Barria, Diego; Drouillas C., Oscar (Estado, Gobierno y Gestión Pública, 2007)
Among the pension system reforms implemented in Latin America since 1981, Argentina stands out as having a less pro-privatization bias, where this result can be explained by thecontext of negotiation between the Carlos Menem government and General Work Confederation (CGT). The paper is intends to provide a suitable analytical explanation to examine the union’sreal chance of having a real influence in the reform being analyzed. It is hypothesized that the CGT was able to influence the formulation of the pension system reform by taking advantage of its political strength, which hinges upon a long lasting relation with the "Justicialista" political party. On top of this, this research argues that the unions demonstrated significant capacity to make use of these political assets.